Implementation of energy-saving modes for electro-radiation drying of oil-containing material using automation tools - Kotov, Borys; Kalinichenko, Roman; Stepanenko, Serhii; Lukach, Vasyl; Hryshchenko, Volodymyr; Kuzmych, Alvian; Pantsyr, Yurii; Garasymchuk, Ihor; Vasylyuk, Volodymyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
For industrial processing of oil-containing plant material, it is necessary to reduce its moisture content to 6–8%. The use of convective, energy-intensive dryers for drying seeds to low moisture levels is inefficient. The aim of the work is to improve the mathematical description of dynamic modes of grain drying in infrared energy supply systems and, based on this, to develop an automatic control system. The main method of researching the static and dynamic characteristics of the grain processing process using infrared radiation is the analytical method followed by experimental verification of the obtained mathematical description. To intensify the process of achieving the desired moisture content of the raw material, it is proposed to use contactless heating with infrared radiation. In this case, the issue of preventing overheating and scorching of the material is resolved by using vibration transportation with particle mixing and automating surface temperature control and its stabilization by adjusting the movement speed. Based on the dependencies, it can be concluded that an increase in the temperature of the grain due to distributed power input enhances the intensity of heating and stabilizes the temperature of the grain material. This leads to a reduction in the time required for the development of moisture gradients within individual grains and speeds up the evaporation of moisture from the surface of the grains. The paper clarifies the mathematical model of thermal processes of infrared processing of oilseeds, on the basis of which an automatic control system was developed for the implementation of energy-saving grain drying modes. The research results showed that the introduction of an automated infrared drying mode allows for a reduction in specific energy consumption by 30-40%.